(untitled) (Педагогіка вищої та середньої школи, 2006)
In the Irina Seregina’s article “The problem of selfregulation & self control in the studying process of pupils” the characteristic of self control as the component of self regulation of pupil’s cognitive activity considered’ the tructure and psychological mechanism of self regulation represented.